PENGEMBANGAN BAHAN AJAR EKONOMI BERBASIS EKONOMI SYARIAH UNTUK SISWA MADRASAH ALIYAH NEGERI KELAS X - Khairuna Arfalah; Eddy Purnomo; Adelina Hasyim (Faculty of Teacher Training and Education, University of Lampung, 2015)
This research aimed to develop teaching materials of economic based syariah economics in class X at Madrasah Aliyah, and to analyze the effectiveness of teaching materials developed. The results of this research was effectiveness test of the normalized gain value comparison, the calculation results showed that the gain in the experimental class of 0.41739 is greater than the gain in the control class is 0.28169, which means the effectiveness of the experimental class is higher than the control class so that the teaching materials is considered effective. In addition the test results obtained by value t Sig. (2-tailed) of 0.012 0.05 (?), in accordance with the basis for a decision in an independent test sample t-test, it can be concluded that H0 rejected and H1 is accepted, which means that there is a difference average of the experimental class and control class, this suggests teaching materials of economy based sharia economics is effective for use in learning.Penelitian ini bertujuan untuk mengembangkan bahan ajar ekonomi berbasis ekonomi syariah pada siswa kelas X pada Madrasah Aliyah, dan menganalisis efektifitas bahan ajar yang dikembangkan. Hasil penelitian ini adalah melalui uji efektifitas perbandingan nilai gain ternormalisasi, hasil perhitungan menunjukkan gain pada kelas eksperimen sebesar 0,41739 lebih besar daripada gain pada kelas kontrol sebesar 0,28169 yang berarti efektifitas kelas eksperimen lebih tinggi dari kelas kontrol sehingga bahan ajar dinilai efektif. Selain itu hasil uji t diperoleh nilai Sig.(2-tailed) sebesar 0,012 0,05 (?), sesuai dengan dasar pengambilan keputusan dalam uji independent sampel t-test , maka dapat disimpulkan H0 ditolak dan H1 diterima, yang artinya terdapat perbedaan rata-rata kelas eksperimen dan kelas kontrol, hal ini menunjukkan bahan ajar ekonomi berbasis ekonomi syariah ini efektif untuk digunakan dalam pembelajaran.Kata kunci: bahan ajar, ekonomi berbasis ekonomi syariah, pengembangan